Perbedaan Kecemasan Primigravida Trimester I Sebelum Dan Sesudah Diberikan Konseling - Erike Septa Prautami (Fakultas Ilmu Kesehatan Universitas Katolik Musi Charitas, 2021)
Anxiety on primigravida one based on deliveries considered synonymous with act it, painful and more erratic than any other events in life. Anxiety more experienced by mother primigravida compared multigravida as much as 66,2%.Aim to know the counseling about pregnancy of anxiety primigravida first trimester. The research is by using this method quasi experimental with pre test- post tests group design. Sample in this research was primigravida pregnant women in Abi Ummi DW Sarmadi Clinic Palembang with 35 respondent, The sample collection technique use Accidental Sampling, and instrument This research using a scale of anxiety Z-SAS. Show average anxiety before was given counseling, 61,94 average anxiety after was given counseling 47.63. Dependent t test of the results obtained the results of no distinction of anxiety before and after primigravida pregnant mothers with counseling p value = 0,00. Providing counseling for pregnant women can reduce anxiety for pregnant women primigravida.